The relationship between kinaesthesia, motor performance, physical fitness and joint mobility in children living in Nigeria - Ebuka Miracle Anieto; Ijeoma Blessing Anieto; Oluwakemi Adebukola Ituen; Niri Naidoo; Charles I. Ezema; Bouwien Smits-Engelsman (BMC Pediatrics, 2023)
Abstract Purpose This study aimed to determine the relationship between kinaesthesia, motor performance, fitness, and joint mobility in children. Methods A descriptive cross-sectional study was conducted involving children from two primary schools in the South-Eastern part of Nigeria. The Beighton criteria were used to measure joint mobility. Motor performance, fitness, and kinaesthesia were measured in all the children. Spearman’s rank correlation was used to evaluate the relationship between the outcomes. Results A total of 91 children (51.6% girls) participated in the study. The mean age of the children was 8.20 ± 1.98 years. Using a Beighton score of ≥ 6, Generalized Joint Hypermobility (GJH) was identified in a total of 35 (38.46%) children and was more prevalent in females (60.0%). Joint mobility had significant correlations with most fitness and motor performance items, but not kinaesthesia. Agility & power, and motor performance seem to be reduced if mobility is larger. Kinaesthesia was correlated with most fitness and motor performance items, indicating that better fitness and better motor performance cooccur with better kinaesthesia or vice versa. Conclusion Joint mobility may have a significant influence on fitness and motor performance in children. Hence, it may be useful for future studies to investigate how fitness and motor performance modulate the onset and progression of musculoskeletal symptoms in GJH.